MANAJEMEN PENDIDIKAN BERBASIS PERILAKU DI SEKOLAH MENENGAH PERTAMA NEGERI 7 MUARO JAMBI - Dini Safitri; Ali Pirdaus; Fransisko Chaniago (STKIP Pesisir Selatan, 2026)
This study aims to describe and analyze behavior-based educational management at State Junior High School 7 Muaro Jambi, encompassing planning, implementation, and evaluation. The background to this research is based on the persistent presence of various deviant student behaviors, such as lack of discipline, violations of school rules, and low respect for teachers and others. This study employed a qualitative, descriptive approach. Data collection techniques included interviews, observation, and documentation. The results of the study indicate that behavior-based education planning is developed collaboratively by involving all elements of the school and is aligned with the school’s vision, mission, and the Merdeka Curriculum. The implementation of behavior-based education management is carried out in an integrated manner through intrakurikuler and ekstrakurikuler activities that are oriented toward developing students’ potential, interests, talents, and positive behavior. Evaluation is conducted regularly and continuously to assess the effectiveness of academic and non-academic programs and their impact on students’ behavior and achievement. The evaluation results are used as a basis for program improvement and the formulation of more effective coaching strategies. Overall, behavior-based education management at Sekolah Menengah Pertama Negeri 7 Muaro Jambi is implemented in a planned, directed, and effective manner in supporting character formation and improving student achievement.